Social Innovation for Conserving Textile-Craft Practices in Boyacá, Colombia (2024)
Social innovation is a strategy for solving problems in community settings that integrates the cooperation of different participants to promote better conditions. This article aims to identify how co-creation practices promote the preservation of artisan textile knowledge through knowledge management and interculturality in social and educational spaces in Nobsa, Boyacá, Colombia. It was a descriptive research that involved a population of textile artisans and students of an educational institution in the community. Focus groups and surveys were used to gather data on specific social aspects of the community under study. Social, educational, and business spaces were created through living laboratories that allowed the search for social alternatives to the pro-blems encountered. As a result, a knowledge management model based on the Nonaka and Takeuchi model was obtained, (1994), which responded to the research objectives and contributed to the reduction of acculturation of textile practices at the local l